Pengaruh Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan LQ45 Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Firmansah, Iqbal Rauf; Sari, Imelda (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Capital structure and profitability are ratios that influence the value of the company. Specifically, the LQ45 Company in the banking sub-sector which is directly controlled by BUMN is an influential company in Indonesia. This research aims to determine the effect of capital structure with the DER ratio and profitability with the ROE ratio on company value with the PBV ratio in LQ45 companies in the banking sub sector. Researchers used quantitative statistical methods and sample determination using a purposive sampling method. The research sample was four companies with a research period of 10 years. The data used in this research is secondary data. Data analysis used the classical assumption test, multiple linear regression analysis, and hypothesis testing using the t test, F test and coefficient of determination using SPSS version 26. The findings of this study show that although profitability has a positive and large impact on company value, capital structure also has a negative and significant impact on company value. In addition, the combination of capital structure and profitability has a significant impact on company value.